2015
DOI: 10.1002/hbm.22747
|View full text |Cite
|
Sign up to set email alerts
|

Resting state functional connectivity of the subthalamic nucleus in Parkinson's disease assessed using arterial spin‐labeled perfusion fMRI

Abstract: Neurophysiological changes within the cortico-basal ganglia-thalamocortical circuits appear to be a characteristic of Parkinson's disease (PD) pathophysiology. The subthalamic nucleus (STN) is one of the basal ganglia components showing pathological neural activity patterns in PD. In this study, perfusion imaging data, acquired noninvasively using arterial spin-labeled (ASL) perfusion MRI, were used to assess the resting state functional connectivity (FC) of the STN in 24 early-to-moderate PD patients and 34 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 97 publications
2
38
1
3
Order By: Relevance
“…A primary strength of this study is the use of ASL, which provides a non-invasive method of directly quantifying blood flow in whole brain or in specific ROIs [26 and 26 and 37 and 38]. Furthermore, temporal fluctuation in CBF (assessed in this case using ASL) appear to correspond to underlying patterns of neuronal activity [26 and 39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary strength of this study is the use of ASL, which provides a non-invasive method of directly quantifying blood flow in whole brain or in specific ROIs [26 and 26 and 37 and 38]. Furthermore, temporal fluctuation in CBF (assessed in this case using ASL) appear to correspond to underlying patterns of neuronal activity [26 and 39].…”
Section: Discussionmentioning
confidence: 99%
“…This step reduces spatial correlations resulting from physiological noise. Specifically, the CBF signal in the ventricles reflects cardiac-induced signal fluctuations while the CBF signal in the white matter reflects the respiratory cycle [26]. CBF volumes were filtered using a low pass (< .07 Hz) filter.…”
Section: Methodsmentioning
confidence: 99%
“…A combined ASL and morphometric study observed a pattern of “parietal cortical thinning and reduced precuneus perfusion” that appeared even in mild PD (Madhyastha et al, 2015: 1). A novel ASL perfusion approach has also been used to examine functional connectivity of the subthalamic nucleus in PD and indicated subthalamic nucleus hyperconnectivity with primary motor cortex and precuneus regions (Fernandez-Seara et al, 2015). …”
Section: Neuroimaging Of Pdmentioning
confidence: 99%
“…These findings suggest that compensatory alterations within the corticostriatal network occur in PD with increased connectivity in the anterior putamen in comparison with the posterior putamen, consistent with the posterior putamen's earlier and greater dopaminergic dysfunction in PD . In addition to striatal network, increased functional connectivity between the subthalamic nucleus and cortex in PD has also been observed (Fernandez-Seara et al, 2015;Kahan et al, 2014). PDD patients showed selective disruption of corticostriatal connectivity (Seibert, Murphy, Kaestner, & Brewer, 2012), specifically, the connectivity of the so-called default mode network, was disrupted in PD patients with cognitive deficits (Disbrow et al, 2014;Gorges et al, 2015).…”
Section: Functional Connectivitymentioning
confidence: 99%